Business cycle synchronization of the Visegrad Four and the European Union - Lubos Hanus; Lukas Vacha (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2015)
In this paper, we map the process of synchronization of the Visegrad Four within the framework of the European Union using the wavelet techniques. In addition, we show that the relationship of output and key macroeconomic indicators is dynamic and varies over time and across frequencies. We study the synchronization applying the wavelet cohesion measure with time-varying weights. This novel approach allows for studying the dynamic relationship among countries from a different perspective than usual timedomain models. Analysing monthly data from 1990 to 2014, the results for the Visegrad region show an increasing co-movement with the European Union after the countries began with preparation for the accession to the European union. The participation in a currency union possibly increases the co-movement. Further, analysing the Visegrad and South European countries' synchronization with the European Union core countries, we find a high degree of synchronization in long-term horizons.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: E32; C40; F15; 330; business cycle synchronization; time-frequency; wavelets; co-movement; Visegrad Four; European Union